2022
DOI: 10.33899/ijvs.2021.130223.1771
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological effects of titanium dioxide nanoparticles on the liver of Japanese quail Coturnix coturnix japonica

Abstract: Titanium dioxide nanoparticles have multiple beneficial uses, as they are used in many medical, industrial, economic, and other fields. Despite these many benefits, it is not without harm to humans and animals if used without control. Therefore, the present study aimed to discover the histopathological effects of Titanium dioxide nanoparticles on the liver of Japanese quail, Coturnix coturnix japonica. The study included three groups, the first group, the control group, which were dosed with distilled water fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…The results of the current study for blood analysis showed that the normal number of RBCs in quail birds was 3.18x10 6 /mm 3 , which agreed with the results of some authors [23,24], they recorded that the number of this type of blood cell was 3.8x10 6 /mm 3 , 3.2x10 6 /mm 3 , respectively. But this result was not agreed with the results obtained by [25], they mentioned that the total normal number of RBC was approximately 2x10 6 /mm3, and Deka and Borah [26], recorded the number was 4.04x10 6 /mm 3 for RBC. The current result also showed that the normal number of WBCs for quail birds in the control group was 5x10 3 / mm 3 , while many researchers [23,24,26] reported that the normal number for WBC ranges between 20-40x10 3 /mm 3 , 24x10 3 /mm 3 , and 3.77x10 3 /mm 3 respectively.…”
Section: Treatmentcontrasting
confidence: 62%
“…The results of the current study for blood analysis showed that the normal number of RBCs in quail birds was 3.18x10 6 /mm 3 , which agreed with the results of some authors [23,24], they recorded that the number of this type of blood cell was 3.8x10 6 /mm 3 , 3.2x10 6 /mm 3 , respectively. But this result was not agreed with the results obtained by [25], they mentioned that the total normal number of RBC was approximately 2x10 6 /mm3, and Deka and Borah [26], recorded the number was 4.04x10 6 /mm 3 for RBC. The current result also showed that the normal number of WBCs for quail birds in the control group was 5x10 3 / mm 3 , while many researchers [23,24,26] reported that the normal number for WBC ranges between 20-40x10 3 /mm 3 , 24x10 3 /mm 3 , and 3.77x10 3 /mm 3 respectively.…”
Section: Treatmentcontrasting
confidence: 62%
“…The measurements were taken with a Color digital camera HMDC-5 coupled to an optical microscope. This camera has built-in image analysis software (Scope image-0.9) to collect these measurements (15,16).…”
Section: Samplingmentioning
confidence: 99%